Ambulatory glucose profile analysis of the juvenile diabetes research foundation continuous glucose monitoring dataset—Applications to the pediatric diabetes population. Issue 7 (23rd November 2016) - Forlenza, Gregory P.; Pyle, Laura L.; Maahs, David M.; Dunn, Timothy C.
Abstract : Background: Increased continuous glucose monitor (CGM) use presents both the benefit and burden of increased data for clinicians to rapidly analyze. The ambulatory glucose profile (AGP) is an evolving a universal software report for CGM data analysis. Objectives/Hypotheses: We utilized the Juvenile Diabetes Research Foundation‐CGM dataset to evaluate the AGP across a broad spectrum of patients to show how AGP can be used clinically to assist with CGM‐related decision making. We hypothesized that AGP metrics would be different across age and HbA1c strata. Subjects: AGPs were generated from the JDRF‐CGM trial dataset for all periods during which there were ≥10 days of CGM coverage in the 2 weeks adjacent to an HbA1c measurement yielding 1101 AGPs for 393 unique subjects. Methods: AGPs were stratified by age group (8‐14, 15‐24, and ≥25 years) and HbA1c (within or above target for age) and compared for between group differences in AGP metrics via two‐factor ANOVA. Glycemic differences between time periods were analyzed via segmented regression analysis. Results: Glucose exposure (average and estimated A1c) and variability (standard deviation and interquartile range) were different between the low and high HbA1c levels. Within a given HbA1c level all age groups were significantly different from each other with older patients having lower averages with less variability than younger patients. Conclusions: AGP analysis of the JDRF‐CGM data highlights significant differences in glycemic profiles between pediatric and adult age groups and between well and less well‐controlled patient populations.